Brain MRI Lesion Load at 1.5T and 3T versus Clinical Status in Multiple Sclerosis - Stankiewicz, James M.; Glanz, Bonnie I.; Healy, Brian C.; Arora, Ashish; Neema, Mohit; Benedict, Ralph H.B.; Guss, Zachary D.; Tauhid, Shahamat; Buckle, Guy J.; Houtchens, Maria K.; Khoury, Samia J.; Weiner, Howard L.; et al. (Journal of neuroimaging, 2011)
ABSTRACT BACKGROUND/PURPOSE To assess correlation between brain lesions and clinical status with 1.5T and 3T magnetic resonance imaging (MRI). METHODS Brain MRI fluid‐attenuated inversion‐recovery (FLAIR) sequences were performed in 32 multiple sclerosis (MS) patients. Expanded Disability Status Scale (EDSS) score (mean ± standard deviation) was 2 ± 2.0 (range 0‐8), disease duration 9.3 ± 8.0 (range .8‐29) years. RESULTS FLAIR lesion volume (FLLV) at 3T was higher than at 1.5T (P= .01). Correlation between 1.5T FLLV and EDSS score was poor, while 3T FLLV correlated moderately and significantly (rs= .39, P= .03). When controlling for age and depression, correlations between FLLV and cognitive measures were significant at 1.5T for the Judgment of Line Orientation test (JLO) (rs=−.44, P= .05), the Symbol Digit Modalities Test (SDMT) (rs=−.49, P= .02), and the California Verbal Learning Test Delayed Free Recall (CVLT DR) (rs=−.44, P= .04). Correlations at 3T were also significant for these tests, but of greater magnitude: JLO (rs=−.70, P= .0005), SDMT (rs=−.73, P= .0001), CVLT DR (rs=−.061, P= .003). Additional significant correlations obtained only at 3T included the 2 second‐paced auditory serial addition test (rs=−.55, P= .01), the Brief Visuospatial Memory Test‐Delayed Free Recall (rs=−.56, P= .007), and the California Verbal Learning Test Total Recall (rs=−.42, P= .05). CONCLUSION MRI at 3T may boost sensitivity and improve validity in MS brain lesion assessment.